The Geography Faculty celebrates its 80 anniversary - Олійник, Я. (Київський національний університет імені Тараса Шевченка, 2012)
The main objectives of the Geography Faculty of the Taras Shevchenko National University of Kyiv development have been highlighted. The history of the Faculty foundation, the contribution of the major scientists and staff in its development, the importance of scientific research have been maintained. The article reveals the history of the foundation of the Geography Faculty departments, determines the role and place of the faculty in the modern scientific and educational process.

Висвітлено основні віхи становлення географічного факультету Київського національного університету імені Тараса Шевченка. Розглянуто історію створення факультету, внесок основних науковців-співробітників у його розвиток, значення наукових досліджень. Розкрито історію заснування кафедр географічного факультету, визначено роль та місце факультету в сучасному освітньому й науковому процесі.
Географічному факультету – 80
Keywords: Geography Faculty; research; educational process; teachers; practice; географічний факультет; дослідження; навчальний процес; викладачі; практики